The Influence of Accounting Knowledge, Business Experience, and Work Motivation on the Perception of Accounting Information Usage - Safitri, Dewi; Subadriyah (Accounting Study Program, Faculty of Economics and Business, 2024)
This research aims to explore the impact of accounting knowledge, business experience, and work motivation on the perception of accounting information utilization, with a focus on MSME participants in Jepara. The study identifies accounting knowledge, business experience, and work motivation as the independent variables, while the dependent variable is the perception of accounting information usage. The data utilized in this research were obtained through primary sources by distributing questionnaires to respondents. The target population comprises MSME business owners in Jepara, with the sample selected through probability sampling using a random sampling approach. A total of 98 respondents were included as the study sample. The analysis was conducted using multiple linear regression techniques processed via SPSS software version 23. The findings reveal that accounting knowledge, business experience, and work motivation significantly and positively influence perceptions regarding the use of accounting information among MSME business owners in Jepara.